L’usage de l’archive comme fondement du pouvoir monarchique : la forêt de papier de la réformation de Froidour (1666-1673) - Sébastien Poublanc (Les Cahiers de Framespa)
October 15, 1661 : Louis XIV signed the decree of the Council of State, imposing the closing of the forests owned by the King, as well as those owned by religious and secular communities. This initiated the greatest reformation the kingdom of France has ever experienced (1661-1680). In order to it carry through, reformers chose to establish a « database » on the relations between local populations and forests. This investigation, involving countless documents of varied natures, revealed the mechanisms of control and appropriation of the territory. Such identification allowed reformers to impose a new framework for territorial control, while it also enabled them to keep a strong hold on a strategic resource : the forest and its products.